2008
DOI: 10.1158/1541-7786.mcr-07-0262
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Class II Phosphoinositide 3-Kinase α Expression below a Critical Threshold Induces Apoptotic Cell Death

Abstract: Members of the phosphoinositide 3-kinase (PI3K) family collectively control multiple cellular responses, including proliferation, growth, chemotaxis, and survival. These diverse effects can partly be attributed to the broad range of downstream effectors being regulated by the products of these lipid kinases, the 3 ¶-phosphoinositides. However, an additional layer of complexity is introduced by the existence of multiple PI3K enzyme isoforms. Much has been learned over the last years on the roles of the classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
7
35
1
Order By: Relevance
“…Fragments representing all three mRNAs were responsive with many fragments being highly efficient in mediating suppression by miR-30e-3p regardless of whether the fragment originated from the open reading frame or the 3 0 UTR (Figure 5c). Of the three targets, we decided to focus on HELZ and PIK3C2A because, unlike WDR44, they have previously been implicated in cellular growth control (Hamamoto et al, 2004;Elis et al, 2008;Ng et al, 2009). As a first step, we confirmed that the miR-30e-3p-mediated suppression of luciferase reporter activity was specific to this miRNA by showing that several other miRNAs, completely lacking seed-matched complementarity to the cloned sequences, were not able to impair luciferase reporter activity (Figure 5d).…”
Section: Wnt Regulation Of Micrornas In Colorectal Cancermentioning
confidence: 71%
See 1 more Smart Citation
“…Fragments representing all three mRNAs were responsive with many fragments being highly efficient in mediating suppression by miR-30e-3p regardless of whether the fragment originated from the open reading frame or the 3 0 UTR (Figure 5c). Of the three targets, we decided to focus on HELZ and PIK3C2A because, unlike WDR44, they have previously been implicated in cellular growth control (Hamamoto et al, 2004;Elis et al, 2008;Ng et al, 2009). As a first step, we confirmed that the miR-30e-3p-mediated suppression of luciferase reporter activity was specific to this miRNA by showing that several other miRNAs, completely lacking seed-matched complementarity to the cloned sequences, were not able to impair luciferase reporter activity (Figure 5d).…”
Section: Wnt Regulation Of Micrornas In Colorectal Cancermentioning
confidence: 71%
“…Recent work has shown that PIK3C2A propagates growth stimuli in cancer cells from different tissues (Elis et al, 2008;Ng et al, 2009), and HELZ has indirectly been associated with proliferation by reportedly being part of a SMYD3-containing growth-promoting protein complex (Hamamoto et al, 2004). Hence, we entertained the possibility that decreased PIK3C2A and HELZ levels were causally involved in restricting cell growth by specifically silencing PIK3C2A and HELZ in DLD1 cells using small interfering RNAs.…”
Section: Downregulation Of Pik3c2a Is Sufficient For Inhibiting Dld1 mentioning
confidence: 86%
“…It is further documented that miR-518a-5p reduced 882R proliferation and promoted 882R apoptosis, and transfection of GIST cells with miR-518a-5p leads to significant PIK3C2A downregulation at the mRNA and protein level. PIK3C2A has been reported to promote tumor survival, 29,30 therefore, low expression of miR-518a-5p is likely to upregulate PIK3C2A and affect the cellular response to the drug, causing resistance to imatinib in GIST. Consequently, our findings may aid in the understanding of miRNA gene regulation with respect to PIK3C2A and their interaction in GIST cells, emphasizing the importance of further studies of the regulative mechanism underlying the miR-518a-5p/PIK3C2A interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Selective engagement of PI3K-p85 by nephrin and CD2AP is known to promote phosphorylation of AKT, which serves as a potent antiapoptotic regulator protecting podocytes from cell death (23). Similarly, inhibition of PI3KC2␣ expression is associated with increased susceptibility to apoptosis and decreased proliferative capacity in various cell types (15,35). Increased expression of the proapoptotic cytokine transforming growth factor ␤ (TGF-␤) has been observed in CD2AP-deficient mice (41).…”
Section: Vol 31 2011 Renal Disease In Pi3kc2␣-deficient Mice 75mentioning
confidence: 99%
“…PI3KC2␣ may also play a role in regulating cell survival. For instance, RNA interference (RNAi)-mediated knockdown of PI3KC2␣ expression induced apoptosis via an intrinsic cell death pathway in HeLa (15) and CHO (26) cells, which was associated with increased levels of activated caspase 9 (15). Data from other recent studies have provided evidence that PI3KC2␣ is a component of diverse cellular processes ranging from neurosecretory granule exocytosis (50) and vascular smooth muscle contraction (53) to insulin signaling (18).…”
mentioning
confidence: 99%